Giant Ovarian Cyst: a Case Report - Mario Joel Arroyo Díaz; Mayelín Díaz Gutiérrez; Miriam García Tirada; Yanara Luisa Gutiérrez Aleaga (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2011)
The giant cysts ovarian growths are rare in the gynecological conditions. We present the case of a patient of 62 years of age, of white color of the skin, weight 73 kg. He came to the General Teaching Hospital "Enrique Cabrera" referring volume increase progressive on the abdomen for a year and a half of evolution without another symptom companion in its beginning, but in recent months caused her lack of air before the efforts, urinated with more frequent than usual and with a lack of appetite. He was diagnosed with cystic mass dependent on ovary, by ultrasonography and computed axial tomography. The practical laparotomy and was resected ovarian cyst left from 21 kg in weight. The anatomopathological study further reported a mucinous cystadenoma ovarian tumor Brenner associated.